PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU EKONOMI SMA NEGERI BREBES - Masruroh, Umi (Universitas Negeri Semarang, 2012)
This research is based on the results of initial observations of economic teachers who showed that economic teacher performance is not optimal. It can be seen from the teachers who are less loyal in his duties because of the low rewards or compensation provided by the school, as well as to obey the teacher’s discipline at the school is still lacking. This study aims to deter-mine influence compensation and the teacher work discipline on the performance of economic teacher partiallyer simultaneously. This study involves a sample of 40 economic teacher. This research type is quantitative correlation approach. The method of data collection by question-naire method. The data analysis method used in this research is descriptive percentage analysis and multiple linear regression analysis. The results of regression analysis shows that there is a partial influence of the compensation on the economic teacher performance at 18,40%, there is a partial effect between the teacher work discipline on the economic teacher performance at 47,47%, there is simultaneous influence among compensation and teacher work discipline on the economic teacher performance at 57,10%. The conclusion partially and simultaneously compensation and teacher work discipline influence on the performance of teacher.